Roof Bolting Anchoring Performance Research on the Entry under the Gob of Close-Distance Coal Seam - Yongjie Yang; Gang Huang; Haiyu Ji (Geofluids)
Seam spacing plays a crucial role in selecting roof bolting of the close-distance coal seam. This work utilized three methods to determine the minimum roof bolting seam spacing of the lower coal seam (LCS) entry after the upper coal seam (UCS) mining. Based on the entry of the No.3-2 coal seam (LCS) in Chaili Coal Mine in China, theoretical analysis, pull-out bolt test, and numerical simulation were performed to calculate the maximum floor failure depth of the UCS and to determine the minimum seam spacing of the roof bolting. The maximum floor failure depth of the UCS determined through theoretical analysis and numerical simulation is 3.2 m and 3.3 m, respectively. In general, the anchorage length of rock bolting is less than 2.4 m, so the minimum seam spacing is 5.6 m or 5.7 m. To further determine the anchorage performance of the roof, the pull-out test was employed on the entry roof of the LCS. When the seam spacing is no less than 6 m, the test results show that the pull-out force of the bolt is more significant than 30kN; in addition, the numerical simulation results indicate that the roof-to-floor and rib-to-rib convergence are relatively small. Therefore, the LCS entry’s minimum roof bolting seam spacing can be determined as 6 m. This study could be used to select and design roof bolting under similar close-distance coal seam conditions.